Enterprise 50: Successful Growing Enterprises of Singapore: An Exploratory Study of Success Factors - Fock, Siew Tong (Institutional Knowledge at Singapore Management University, 2001)
The Enterprise 50 (E-50) award is a recognised hallmark of excellence accorded by the Singapore Economic Development Board in conjunction with Andersen Consulting and Business Times to successful growing enterprises (SGEs) in Singapore. The E-50 companies are deemed to play an important role in the development of ''an external economic wing'' in Singapore's economic development, in line with the nation's desire to internationalise its local enterprises. The availability of a pool of E-50 companies provides an opportunity to study their growth process, business practices and strategies which are often regarded to be success factors for enterprises. This paper reports on the findings from four case studies of E-50 companies. The findings reveal that they follow a discernible pattern of sequence of stages as they develop and grow, with the founder being the most important asset in the start-up stage and the survival stage. The findings also suggest that the success factors hinge on the entrepreneur's personality and experience in the start-up and survival stages, and on the success of his managerial role in the subsequent stages. Six success factors - revealed by the entrepreneurs in this study as entrepreneurial, marketing, operational, financial, competitive strategy and management - were associated with the successful performance of E-50 companies. Having a successful start, early identification of source(s) of competitive advantage and effective managerial pursuit to its sustenance has provided the road map for their success. While the assistance package of the Singapore government complements the founders¡¦ efforts to acquire the capability to compete in the international markets, the choice to be a growing business resides with the founders of these local enterprises.